Comparative education the dialectic of the global and the local - Arnove, Robert F.; Torres, Carlos Alberto (Rowman & Littlefield, 2003)
Bringing together some of the leading names in comparative and international education, this second edition provides new perspectives on the dynamic interplay of global, national and local forces as they shape education systems in specific contexts.